2023
DOI: 10.1080/02670836.2023.2176621
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation behaviour and strengthening mechanisms of V-bearing 1800 MPa grade hot-stamping steel

Abstract: Achieving strength-ductility synergy of hot-stamping steel via microalloying technology has attracted great attention due to their pronounced precipitation strengthening. Nevertheless, the precipitation behaviours and characteristics have not been clearly unveiled. In this work, the effects of V content on the microstructure and mechanical properties of 1800 MPa grade hot-stamping steel are systematically studied. Massive V contained precipitates develop after hot-rolling and coiling, which refine the martensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Generally, the steel grade and strength level of traditional Mn-B steel is determined by the C content, as presented in Table 1 . For example, 30MnB5 and 34MnB5 have C contents of 0.30–0.31 wt% and 0.33–0.34 wt%, respectively, and their corresponding tensile strength can reach 1880 MPa and 1980 MPa [ 20 , 39 ]. More recently, there have also been considerable research efforts devoted to developing PHS with even higher strength, such as 0.38% C content corresponding to a tensile strength of 2181 MPa [ 10 ].…”
Section: Traditional Mn-b Steelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the steel grade and strength level of traditional Mn-B steel is determined by the C content, as presented in Table 1 . For example, 30MnB5 and 34MnB5 have C contents of 0.30–0.31 wt% and 0.33–0.34 wt%, respectively, and their corresponding tensile strength can reach 1880 MPa and 1980 MPa [ 20 , 39 ]. More recently, there have also been considerable research efforts devoted to developing PHS with even higher strength, such as 0.38% C content corresponding to a tensile strength of 2181 MPa [ 10 ].…”
Section: Traditional Mn-b Steelsmentioning
confidence: 99%
“…These elements are strong carbide formers [ 45 , 46 ] and tend to segregate [ 47 ] at interphase, which can cause a precipitation-strengthening effect and solute drag in PHS [ 48 ]. In our recent work, the precipitation behavior of microalloying elements in PHS is unveiled [ 20 ]. It is found that the microalloyed carbides mainly precipitate during hot rolling and coiling, as a result of the low solid solubility of microalloying carbides in ferrite.…”
Section: Traditional Mn-b Steelsmentioning
confidence: 99%
See 3 more Smart Citations